Effect of macromolecular crowding on the kinetics of glycolytic enzymes and the behaviour of glycolysis in yeast - Thoke, Henrik S. (2018)
Water is involved in all aspects of biological activity, both as a solvent and as a reactant. It is hypothesized that intracellular water is in a highly structured state due to the high concentrations of macromolecules in the cell and that this may change the activity of intracellular enzymes due to altered binding affinities and allosteric regulations. Here we first investigate the kinetics of two glycolytic enzymes in artificially crowded aqueous solutions and show that crowding does indeed change their kinetics. Based on our kinetic measurements we propose a new model of oscillating glycolysis that instead of Michaelis-Menten or Monod-Wyman-Changeux kinetics uses the Yang-Ling adsorption isotherm introduced by G. Ling in the frame of the Association-Induction (AI) hypothesis. Using this model, we can reproduce previous experimental observations of the coupling of glycolytic oscillations and intracellular water dynamics, e.g., (i) during the metabolic oscillations, the latter variable oscillates in phase with ATP activity, and (ii) the emergence of glycolytic oscillations largely depends on the extent of intracellular water dipolar relaxation in cells in the resting state. Our results support the view that the extent of intracellular water dipolar relaxation is regulated by the ability of cytoplasmic proteins to polarize intracellular water with the assistance of ATP, as suggested in the AI hypothesis. This hypothesis may be relevant to the interpretation of many other biological oscillators, including cell signalling processes.